Changing the drug development and therapeutic paradigm with biologic drug combinations and bispecifics: How to choose between these two approaches? - Songmao Zheng; Rodney Prell; Jennifer Sheng; Yow‐Ming Wang; Lora Hamuro (Wiley, 2022)
Abstract Biologics are increasingly being co‐developed in combination or as novel constructs like bispecific antibodies (BsAbs) with the goal of targeting multiple, non‐redundant mechanisms of action. Rational design of combinations and dual‐targeting approaches that consider disease complexities have the potential to improve efficacy and safety, to increase duration of clinical benefit, and to minimize clinical resistance mechanisms. Here we summarize examples of BsAbs and biologic combinations that have been approved by health authorities and present drug development considerations when deciding between these two strategies. These include an understanding of target biology, nonclinical safety risks, dose optimization strategies, the regulatory framework, pharmacokinetic, immunogenicity, and bioanalytical assay considerations. The disease biology, target dynamics, and pharmacology objectives were identified as important factors in early drug development to decide between a BsAb versus a combination. Nonclinical safety assessment and dose optimization strategies can also pose challenges for BsAb versus combinations. High unmet medical needs and lack of treatment options are often the common denominators for deciding to develop a BsAb or a combination. Future development of biologic triple combinations and BsAbs combinations with other biologics will further increase drug development complexities and hold promise for more effective treatment options for patients.